Os efeitos expansivos das transferências intergovernamentais e o efeito transbordamento das despesas públicas dos municípios brasileiros : um estudo com dados em painel para o período de 2010-2015 - Santos, Fladia Valeria Dantas dos (2018)
The main objective of this dissertation is to study the expansive effects of the intergovernmental transfers (flypaper effect) and the spillover effect of the public expenditures of the Brazilian municipalities, from 2010 to 2015, through the use of panel data. In order to meet this objective, initially, in order to build the theoretical bases of the study, the paper used the empirical and theoretical literature of fiscal federalism focused on the flypaper effect and the spillover effect; then through the descriptive analysis of data, the interregional and intra-regional disparities characterizing Brazil and the municipal public finances were evidenced, and consequently the implications of these characteristics for the Brazilian federal system; and finally, the work used the econometric model, through the System GMM estimator to test the existence of the studied phenomena. The main results showed that: there are dynamics in the municipal expenses with their past value being related to the present value; the GDP had a positive effect on the dependent variable; for lump sum type transfers, only the part of FPM and ICMS had a positive impact on the dependent variable; the expenditure of neighboring municipalities had a positive effect on total expenditure; and, structural factors also had a positive effect on the dependent variable. These results confirm the existence of the flypaper effect (through the effects of the FPM) and the spillover effect (through the neighbor expenditure variable) in the public finances of Brazilian municipalities.